Identifikasi Potensi Interaksi Obat pada Peresepan Pasien Rawat Jalan Diabetes Melitus Tipe 2 dengan Hipertensi di RSUD dr. Soediran Mangun Sumarso Wonogiri - Syahrullah Murwati, Isna; Murtisiwi, Lusia (Jurnal Farmasi (Journal of Pharmacy), 2021)
This study aims to determine the prescription profile of diabetes mellitus type 2 with hypertension include classes and types of drugs and the potential of drug interactions theoretically, based on the mechanism drug interactions in outpatient installation of RSUD dr. Soediran Mangun Sumarso Wonogiri 2018. This research is a non-experimental study with descriptive retrospective. The data collected from medical records of patients between period January-June 2018 are identified based on the literature and processed by calculating the percentage. Class of diabetes drugs most widely used is a sulfonylurea (19,64%) and hypertension drug classes ARB (19,03%). Types of diabetic drugs most widely used was glimepirid (17,33%) and hypertension was irbesartan ( 17,21%). The percentage result of drug interactions theoretically was 62% (106 patiens), drug interactions type that the most occured was pharmacodynamic interactions 64,5%.